CONCEPTUAL METAPHORS OF WORLD CUP 2022 QATAR NEWS TEXTS ON ARABIYA NEWS WEBSITE - Mellinda Raswari Jambak; Moh Zawawi (LLDIKTI Wilayah X, 2023)
Many new languages have emerged according to the times. At the same time, linguists then gave rise to various linguistic studies related to perceived difficulties. This study discusses words or sentences that are used metaphorically. The aims of this study were to (1) identify structural metaphors in the 2022 Qatar world cup news on the Arabiya News website, (2) identify orientalist metaphors in the 2022 Qatar world cup news on the Arabiya News website, and (3) identify ontological metaphors in the cup news world 2022 Qatar on the news website Arabiya News. The method used is descriptive qualitative. The data collection technique uses the observing and note-taking technique, while the data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and concluding. The results of the study obtain 9 data, namely 3 data on structural metaphors, 4 data on orientalist metaphors, and 2 data on ontological metaphors. Knowledge about word diversity is important to know, because with it we can expand our vocabulary. This research is useful to increase knowledge related to some vocabularies that contains metaphors.